Moscow, Havana and asymmetry in international relations. Issue 3 (2nd July 2016) - Bain, Mervyn
Abstract: Asymmetric relationships have been fundamental to the study of international relations, becoming even more important with the end of the Cold War, which left the United States as the sole global superpower. However, what impact does the distance between two countries have on the magnitude of an asymmetric relationship and the exposure of the countries to one another? This article examines these phenomena by analysing the relationship between Havana and Moscow from the time of the Russian Revolution in November 1917 to the present. Specifically it examines three distinct periods: from November 1917 until February 1960, from February 1960 until the implosion of the Soviet Union in late 1991 and from 1992 to the present. This article posits that the distance between two countries reduces neither the intensity of an asymmetric relationship nor the exposure of the two countries to one another.